Two Cases of Miliary Tuberculosis and Increasing Level of CA-125 - M Alimagham; S Aminiafshar; SMM H Moghaddam; S Shokuhi (Canadian Journal of Infectious Diseases and Medical Microbiology)
Two cases of miliary tuberculosis and elevated levels of cancer antigen 125 Ovarian carcinoma is one of the most dangerous malignancies in women. The serum level of cancer antigen (CA) 125, as a tumour marker, is useful in the diagnosis of ovarian cancer. CA 125 serum level is also elevated in ascites (1), ovarian tube abscess (2,3), biliary duct cancer and periampullary tumours (4), cholangitis (5), cancer of pancreas (6) and cervical adenocarcinoma (7). Additionally, sometimes the serum level of CA 125 increases spontaneously during the menstrual cycle (8,9). In bone marrow transplantation, this marker is a sensitive index in the diagnosis of veno-occlusive disease (10). We describe an elevated serum level of CA 125 in two cases of tuberculosis (TB): one with cryptogenic miliary TB, and the other with miliary TB and meningitis.